Islam Kâffah: Tinjauan Tafsir Q.S. Al-Baqarah: 208 - Ahmadiy Ahmadiy (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2016)
Mukti Ali emphasizes the importance of seeing Islam kâffah. In this relationship Mukti Ali says, if we see Islam just of one facet, we will only see one dimension and phenomenons that is multi facet, even if we see it is correct. The Islam terminologicals has comprehended kâffah, which is Islam grasp that done by komprehensif's. Nasruddin Razak also opines that understanding Islam kâffah are important, so that could become qualified followers of the religion and for growing regarding attitude for other religion followers. That trick also been sailed through in the effort avoid miss understanding that can evoke attitude and life pattern gets incorrect religion.